MUSKAR-T for Improving Mental Health and Cancer-Related Symptoms in Women Diagnosed with Breast Cancer Undergoing Chemotherapy: A Queasy Experimental Design - Anggraini, Dian; Dewi Marfuah; Susy Puspasari; Lia Juniarni (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Women diagnosed with breast cancer suffer from significant psychological distress, mainly depression and anxiety, fatigue, and sleep disturbance. The effects of music therapy and progressive muscle relaxation training on the quantity and quality of sleep, as well as on levels of anxiety and fatigue, in patients undergoing chemotherapy for breast cancer. Objectives: The aim of the study was to determine the effects of MUSKAR-T (combination of music therapy and progressive muscle relaxation training) on sleep quality, anxiety, and fatigue in breast cancer patients undergoing chemotherapy. Methods: The study employed a two-group, pre- and post-test experimental design. Patients in the intervention group had two sessions of 30-minutes of music therapy and progressive muscular relaxation per day for five days prior to hospital discharge. Pittsburgh Sleep Quality Index (PSQI), State Trait Anxiety Index (STAI), and Cancer-related Fatigue Assessment (C-RAFA) were used to evaluate the results (CFS). Anxiety, tiredness, and sleep quality were measured and compared between groups using a univariate approach that also took into account the effects of group, time, and the interaction of group and time. Results: This study had 100 participants, 50 in the intervention group and 50 in the control group. The majority of respondents were married (70 percent), unemployed (24 percent), had completed at least middle school (68 percent), were not menopausal (76 percent), and had illness at stage III (46 percent ). The intervention group’s anxiety, fatigure, and sleep quality scores fell to 76.1112.42, 45.1214.76, and 4.363.36 on the day preceding hospital discharge. Conclusions: The culturally-based music therapy and progressive muscle relaxation effective for reducing anxiety, fatigue, and enhancing the quality of sleep in breast cancer patients undergoing chemotherapy.